PERLINDUNGAN TERHADAP ANAK DALAM SISTEM PERADILAN PIDANA INDONESIA - Supriyanto - (Wacana Hukum, 2011)
Abstract : Law No. 3 Year 1997 on Juvenile Court governing the protection of children by giving preferential treatment on juvenile delinquents, but the imposition of penalty is not the only effort to educate juvenile delinquents. Forward required the criminal justice system for children is not oriented to punishment but rather aim to educate and nurture children for the welfare of juvenile delinquents. Keywords : criminal justice system, child protection